P2Y Receptors in the Mammalian Nervous System: Pharmacology, Ligands and Therapeutic Potential - Weisman, Gary A. (CNS Neurol Disord Drug Targets, 2012)
P2Y receptors for extracellular nucleotides are coupled to activation of a variety of G proteins and stimulate diverse intracellular signaling pathways that regulate functions of cell types that comprise the central nervous system (CNS). There are 8 different subtypes of P2Y receptor expressed in cells of the CNS that are activated by a select group of nucleotide agonists. Here, the agonist selectivity of these 8 P2Y receptor subtypes is reviewed with an emphasis on synthetic agonists with high potency and resistance to degradation by extracellular nucleotidases that have potential applications as therapeutic agents. In addition, the recent identification of a wide variety of subtype-selective antagonists is discussed, since these compounds are critical for discerning cellular responses mediated by activation of individual P2Y receptor subtypes. The functional expression of P2Y receptor subtypes in cells that comprise the CNS is also reviewed and the role of each subtype in the regulation of physiological and pathophysiological responses is considered. Other topics include the role of P2Y receptors in the regulation of blood-brain barrier integrity and potential interactions between different P2Y receptor subtypes that likely impact tissue responses to extracellular nucleotides in the CNS. Overall, current research suggests that P2Y receptors in the CNS regulate repair mechanisms that are triggered by tissue damage, inflammation and disease and thus P2Y receptors represent promising targets for the treatment of neurodegenerative diseases.